Emerging trends in the development and application of composite indicators - Jeremic, Veljko, 1985-; Radojicic, Zoran, 1967-; Dobrota, Marina, 1984- (Hershey, PA : Information Science Reference, 2017)
'This book is an authoritative reference source for the latest scholarly research on the benefits and challenges presented by building composite indicators, and how these techniques promote optimized critical thinking'--
Includes bibliographical references and indexes.
Keywords: Statistics; Economic indicators; Social indicators; Political indicators; Science indicators